2019
DOI: 10.3390/nu11122899
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sleep with Food Cravings, Diet, and Obesity in Adolescence

Abstract: Background: Sleep and dietary intake/quality can contribute to excess weight gain, but food cravings may influence these relationships. This cross-sectional study examined the relationship of adolescents' sleep characteristics with dietary intake/quality and obesity and whether food cravings mediated these relationships. Methods: Sleep measures were calculated based on 24-h accelerometry, and height and weight were directly measured to calculate body mass index (BMI) z-scores. Food cravings were assessed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 55 publications
(77 reference statements)
1
22
1
1
Order By: Relevance
“…Consecutive nights of short sleep duration (5 h) have also been shown to increase food intake in excess of the energy an individual requires, another potential contributor to the weight gain observed in shift workers [30]. Our finding that short sleep duration is associated with more food cravings is also consistent with other cross-sectional studies [20,31].…”
Section: Discussionsupporting
confidence: 91%
“…Consecutive nights of short sleep duration (5 h) have also been shown to increase food intake in excess of the energy an individual requires, another potential contributor to the weight gain observed in shift workers [30]. Our finding that short sleep duration is associated with more food cravings is also consistent with other cross-sectional studies [20,31].…”
Section: Discussionsupporting
confidence: 91%
“…Os achados podem sugerir que o ritmo circadiano possui influência na alimentação e que um comportamento alimentar positivo depende de uma duração de sono alinhada ao relógio biológico do adolescente 57 . Estudo realizado por Kracht et al 58 mostrou que quanto maior a duração do sono dos adolescentes menor o desejo por alimentos doces e gordurosos.…”
Section: ≥12unclassified
“…Findings from the few studies examining the association between sleep and food cravings, or food craving‐related constructs (e.g., desire for food and food appeal) in youth are inconsistent. For example, Kracht et al 16 cross‐sectionally analysed multiple facets of sleep and frequency of food cravings and found that sleep efficiency (i.e., the proportion of time one is asleep while lying in bed), but not sleep duration or variability, was related to cravings for foods high in fat and carbohydrates. Yet, preliminary experimental studies among adolescents have linked earlier bedtimes to lower desires for sweet foods 17 and shorter sleep duration to increased desires for sweets 18 .…”
Section: Introductionmentioning
confidence: 99%